Endovascular Treatment for Acute Large Vessel Occlusion Due to Underlying Intracranial Atherosclerotic Disease - Huo, Xiaochuan; Sun, Dapeng; Chen, Wenhuo; Han, Hongxing; Abdalkader, Mohamad; Puetz, Volker; Yi, Tingyu; Wang, Hao; Liu, Raynald; Tong, Xu; Jia, Baixue; Ma, Ning; Gao, Feng; Mo, Dapeng; Yan, Bernard; Mitchell, Peter J.; Leung, Thomas W.; Yavagal, Dileep R.; Albers, Gregory W.; Costalat, Vincent; Fiehler, Jens; Zaidat, Osama O.; Jovin, Tudor G.; Liebeskind, David S.; Nguyen, Thanh N.; Miao, Zhongrong (Seminars in Neurology, 2023)
Intracranial atherosclerotic disease (ICAD) is one of the most common causes of acute ischemic stroke worldwide. Patients with acute large vessel occlusion due to underlying ICAD (ICAD-LVO) often do not achieve successful recanalization when undergoing mechanical thrombectomy (MT) alone, requiring rescue treatment, including intra-arterial thrombolysis, balloon angioplasty, and stenting. Therefore, early detection of ICAD-LVO before the procedure is important to enable physicians to select the optimal treatment strategy for ICAD-LVO to improve clinical outcomes. Early diagnosis of ICAD-LVO is challenging in the absence of consensus diagnostic criteria on noninvasive imaging and early digital subtraction angiography. In this review, we summarize the clinical and diagnostic criteria, prediction of ICAD-LVO prior to the procedure, and EVT strategy of ICAD-LVO and provide recommendations according to the current literature.
Keywords: intracranial atherosclerotic disease; intracranial stenosis; large vessel occlusion; endovascular therapy; intracranial stenting; balloon angioplasty; rescue stenting